Anticancer Effects of Extracts from Three Different Chokeberry Species. (10th June 2021) - Gill, Navpreet K.; Rios, Diana; Osorio-Camacena, Elena; Mojica, Benigno E.; Kaur, Baljinder; Soderstrom, Matthew A.; Gonzalez, Maricarmen; Plaat, Brandy; Poblete, Clarice; Kaur, Navdeep; Singh, Henna; Forester, Sarah C.
Abstract: Colon cancer risk appears to be lowered by consumption of a diet rich in fruits and vegetables. Chokeberries are rich in phytochemicals that may act as potent anticancer agents. Phytochemicals that are particularly abundant in chokeberries include anthocyanins and phenolic acids. In this study, we compared the growth inhibitory activity of three chokeberry extracts in HT-29 human colon cancer cells. The three extracts tested were derived from Aronia arbutifolia (red), Aronia prunifolia (purple), and Aronia melanocarpa (black). Cells were incubated with either red, purple, or black chokeberry extracts and cell viability was quantified using the thiazolyl blue tetrazolium bromide (MTT) assay. The black chokeberry extract had the greatest effect in reducing cell proliferation. The extracts were also characterized for total phenols (Folin-Ciocalteu assay), total antioxidant activity (oxygen radical absorbance capacity assay), and levels of bioactive phenolic acids (high-performance liquid chromatography). The growth inhibitory activities of the extracts correlated well with total phenolic content, antioxidant activity, and levels of caffeic and chlorogenic acids. The black chokeberry extract had the greatest level of total phenols, antioxidant activity, and individual phenolic acids. This research suggests that the phenolic profile of foods such as chokeberries can help determine their cancer cell growth inhibitory activity.